Morphological variability of seeds in East African species of the genus Hypoxis L. (Hypoxidaceae) - Wiland-Szymańska, Justyna (Biodiversity: Research and Conservation, 2025)
Morphology and types of the seed testa sculpture in the East African taxa of the genus Hypoxis were investigated. Studies have revealed that there are 9 types of the seed testa sculpture in the East Tropical Africa. Distribution of types of seed testa sculpture is unequal among the taxa studied. Some are wide spread and some confined to a single species or variety. Morphology of the seed testa sculpture is a useful taxonomic character for determination of taxa of the genus Hypoxis in the East Africa.